Transverse laxity of the forefoot. Issue 1 (January 2022) - Robberecht, Joris; Decroocq, Lauryl; Schramm, Martin; Gabay, Ari; Maestro, Michel
Highlights: Transverse laxity is an easy sign to stage the progressive forefoot destruction. In presence of major transverse laxity a plantar plate lesion should be suspected. In cadaveric feet a plantar plate repair is able to correct transverse stability. Soft tissue procedures should be considered in addition to bone correction. Abstract: Background: Splay of the forefoot reflects the loss of tension in the soft tissues and indicates failure of the biomechanics of the tie-bar system. By identifying and quantifying the soft tissue structures involved in the destruction of forefoot stability we could increase the understanding of forefoot pathologies. Methods: We investigated the transverse forefoot laxity on healthy feet, feet with forefoot pathology and cadaveric feet undergoing sequential dissection. Results: Statistical difference in transverse laxity was seen between healthy feet (n = 160) and feet with symptomatic forefoot pathology requiring surgery (n = 29). Presence of lesser ray pathology is associated with increased transverse laxity. For the dissected cadaveric feet (n = 9) sequential sectioning the plantar plate causes a progressive evolution of transverse laxity. The repair of plantar plates greatly improves transverse stability. Conclusions: Forefoot pathology causes increased transverse laxity. In case of a major transverse laxity of the forefoot a plantar plate lesion should be suspected.